Boundaries and barriers: Racialized dynamics of political power. Issue 10 (October 2016) - Rosino, Michael L.
Abstract: Recent sociological works establish the significance and role of the state and political sphere in the enactment of racial oppression and construction of racial categories. However, less understood are the racialized dynamics that mediate exclusion and access to political power, particularly at the meso‐ and micro‐levels. Synthesizing extant theory and research on racial inequality, the state, politics, and power, this article advances a framework centering on boundaries and barriers. First, it discusses the relationship between the state and political sphere, political power, and racial inequality. Next, it explores the literature on the deployment and contestation of racialized boundaries to the symbolic and material benefits of the state. It then examines the literature on racialized barriers to engagement, participation, and influence in the political sphere. The article concludes by suggesting future research in the related areas of agenda‐setting and influence and the microdynamics of political power.